Next generation technology to minimize ecotoxicity and to develop the sustainable environment: White Biotechnology - Sang, Byoung-In; Ryu, Jae-Chun (KOREAN SOC TOXICOGENOMICS & TOXICOPROTEOMICS, 2005)
This review aims to show that industrial sustainable chemistry, minimizing or reducing the ecological impacts by the chemicals, is not an emerging trend, but is already a reality through the application of 'White Biotechnology' such as 'green' chemistry and engineering expertise. A large number of current industrial case studies are presented, as well as new developments from the chemical industry. The case studies cover new chemistry, new process design and new equipment. By articulating the requirements for industrial application of sustainable chemistry, this review also seeks to bridge any existing gap between academia and industry regarding the R & D and engineering challenges needed to ensure green chemistry research enables a more sustainable future chemical industry considering eco-toxicological impacts.
Keywords: GENE-EXPRESSION; IDENTIFICATION